THE REVENUE AND INCOME PRINCIPLES. - Dohr, James L. (The Accounting Review, 1942)
Abstract While it is entirely proper, for purposes of discussion, that the American Accounting Association's statement of accounting principles underlying corporate financial statements be divided into parts, no section or part of the statement can be intelligently discussed without considering the statement in its entirety. The original or tentative statement was predicated by its authors on the assumption that corporate financial statements should be continuously in accord with a single coordinated body of accounting theory. The same idea is indicated in the revision, where the achievement of the desired objectives in accounting is said to be dependent upon the existence of a unified and coordinated body of accounting theory. Every part of the statement must therefore be considered in the light of its relationship to the whole. Rules found to be unsatisfactory were changed as conditions indicated the necessity therefore, the charge has frequently been made that the system failed to keep abreast of social and economic developments.